Economic Analysis of Fisher Households: Income, Expenditure and Economic Sustainability in the Coastal Area of Karanrang Island, Pangkajene and Kepulauan Regency - Mustari; Alwi, M. Rasdul; Nurdiana; Rijal, Syamsu (ADMAN: Journal of Contemporary Administration and Management, 2024)
This study aims to analyze the economy of fisher households both from income, expenditure and economic sustainability in the coastal area of Karanrang Island, Pangkajene dan Kepulauan Regency. This research used a survey method with a quantitative descriptive approach to answer the first and second problem formulations, and a qualitative approach to answer the third problem formulation. This study took 28 samples of fishermen household actors in the Karanrang Island Coastal Area from 73 households in the population with an error rate of 10% using simple random sampling. The data collection techniques used were observation, interview and documentation. The results showed that the total income of fishermen households in the coastal area of Karanrang Island, Pangkajene dan Kepulauan Regency amounted to IDR 4,576,680 / month with the contribution of fishermen's income by 56% affecting income, for fishermen's household expenditure on average spent IDR 3,895,179 / month for food expenditure with a proportion of expenditure of 72% and the economic sustainability of fishermen households analyzed from the concept of blue economy can be said to continue in economic and social aspects but there needs to be special attention to ecological / environmental aspects. It is expected that the economic actors of fisher households can maximize their income either from the fisheries sector or from non-fishermen. It is expected that fishermen can manage and utilize fishery resources wisely and responsibly. It is expected for the government to pay more attention to the people in the Coastal Zone. Then, for researchers to be able to develop this research and be able to be continued by other researchers to conduct more in-depth research on income, expenses and economic sustainability in the Coastal Zone. This research supports and strengthens the findings of previous studies. The results provide an overview of the economic situation of household actors in terms of income, expenditure and economic sustainability in the region.